Method for recycling solid electrolyte in all-solid-state lithium ion battery by using eutectic solvent

Through the use of low eutectic solvents, the complexity and low efficiency of solid electrolyte recycling of lithium-ion batteries have been solved, efficient and environmentally friendly metal recycling has been achieved, resource waste and environmental pollution have been reduced, and it is in line with the concept of sustainable development.

CN119231009APending Publication Date: 2024-12-31LANGFANG NORMAL UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411588256.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The recycling methods of solid electrolytes in existing lithium-ion batteries are complex and inefficient, resulting in waste of resources and environmental pollution.

Method used

The hydrogen bond donor and hydrogen bond acceptor are stirred and mixed with eutectic solvents to dissolve and recover solid electrolytes in all-solid lithium-ion batteries. The efficient recovery of metals is achieved through leaching and centrifugation processes. The solvent used is green. Environmentally friendly, easy to operate and low cost.

Benefits of technology

It realizes efficient recycling of solid electrolytes in lithium-ion batteries, reduces resource waste and environmental pollution, conforms to the concept of sustainable development, and is simple to operate and has low energy consumables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005124849270000061
    Figure BDA0005124849270000061
Patent Text Reader

Abstract

The invention discloses a method for recycling a solid electrolyte in an all-solid-state lithium ion battery by using a deep eutectic solvent, belongs to the field of catalytic chemistry, and aims to solve the problems that the existing recycling mode for recycling the solid electrolyte of the lithium ion battery is complicated in operation and relatively low in recycling rate in the prior art. The method comprises the following steps: 1) stirring and mixing a hydrogen bond donor and a hydrogen bond acceptor to obtain a eutectic solvent; 2) weighing an all-solid-state lithium ion battery electrolyte, and dissolving the weighed all-solid-state lithium ion battery electrolyte in the eutectic solvent for leaching; (3) after the reaction in the step (2) is finished, obtaining a mixture, and centrifuging the mixture to obtain a supernatant and a lower-layer mixture II; in the step 1), the hydrogen bond donors are acids, phenols, alcohols, salts or ketones, and the hydrogen bond acceptors are polyethylene glycol 200, choline chloride or amino acids. The method has the advantages that the method is simple and easy to operate, low in cost, low in energy consumption, green and environment-friendly, and the solvent is high in designability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for recovering solid electrolyte in an all-solid-state lithium-ion battery by utilizing a low eutectic solvent, and belongs to the field of catalytic chemistry. Background Art

[0002] Solid-state batteries are a type of battery technology. Unlike the lithium-ion batteries and lithium-ion polymer batteries commonly used today, solid-state batteries are batteries that use solid electrodes and solid electrolytes. Since the scientific community believes that lithium-ion batteries have reached their limits, solid-state batteries have been seen in recent years as batteries that can succeed lithium-ion batteries. Solid-state lithium battery technology uses glass compounds made of lithium and sodium as conductive materials to replace the electrolyte of previous lithium batteries, greatly improving the energy density of lithium batteries.

[0003] With the widespread application of lithium-ion batteries in electric vehicles, smart phones, energy storage systems and other fields, their production and waste are also increasing. Lithium-ion batteries are entering a "decline period", and the recycling of waste lithium-ion batteries has become a hot research topic in recent years. The main components of lithium-ion batteries include positive electrode materials, negative electrode materials, solid electrolytes and electrolytes. For the recycling of solid electrolytes of lithium-ion batteries, the existing recycling methods are cumbersome and have a low recovery rate. If the solid electrolytes of lithium-ion batteries cannot be recycled efficiently, improper recycling and treatment will cause environmental problems such as waste of resources or soil pollution. Summary of the invention

[0004] The present invention provides a method for recovering solid electrolytes in all-solid-state lithium-ion batteries by utilizing a low eutectic solvent. The method is simple, convenient, and easy to operate, has low raw material costs, low energy consumption, and is green and environmentally friendly. The solvent is highly designable and has high practical application value and promotion value.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is a method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent, comprising the following steps:

[0006] 1) stirring and mixing a hydrogen bond donor and a hydrogen bond acceptor to obtain a deep eutectic solvent;

[0007] 2) weighing an all-solid-state lithium-ion battery electrolyte, and dissolving the weighed all-solid-state lithium-ion battery electrolyte into a deep eutectic solvent for leaching;

[0008] 3) After the reaction in step 2) is completed, a mixture is obtained, and the mixture is centrifuged to obtain an upper clear liquid and a lower mixture II;

[0009] In step 1), the hydrogen bond donor is an acid, a phenol, an alcohol, a salt or a ketone, and the hydrogen bond acceptor is polyethylene glycol 200, choline chloride or an amino acid.

[0010] Optimized, in the above method of recovering solid electrolytes in all-solid-state lithium-ion batteries using a deep eutectic solvent, the hydrogen bond acceptor is one of polyethylene glycol 200, choline chloride, L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine;

[0011] The hydrogen bond donor is one of benzoic acid, oxalic acid, phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, lactic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzenediol, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, ethanol, methanol, zinc chloride, ferric chloride, and acetylacetone.

[0012] Optimized, the above-mentioned method of recovering solid electrolytes in all-solid-state lithium-ion batteries using low eutectic solvents, the all-solid-state lithium-ion battery electrolyte includes lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide and aluminum-doped lithium lanthanum zirconium oxide.

[0013] Optimized, in the above method of recovering solid electrolytes in all-solid-state lithium-ion batteries using a low eutectic solvent, when leaching is performed in step 2), the leaching temperature is 25 degrees Celsius to 120 degrees Celsius, and the leaching time is 0.17 hours to 48 hours.

[0014] Optimized, the above method of recovering solid electrolyte in all-solid-state lithium-ion battery using deep eutectic solvent, after step 3), metal recovery is performed from the supernatant, and the specific process includes:

[0015] Equal volumes of the supernatant and antisolvent were mixed and sonicated for 20 minutes, followed by standing for 24 hours.

[0016] Optimized, in the above method of recovering solid electrolytes in all-solid-state lithium-ion batteries using a deep eutectic solvent, when the hydrogen bond acceptor is polyethylene glycol 200 and the hydrogen bond donor is one of phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzenediol, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, zinc chloride, ferric chloride, and acetylacetone, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6;

[0017] When the hydrogen bond acceptor is polyethylene glycol 200 and the hydrogen bond donor is one of benzoic acid and oxalic acid, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6-1:14;

[0018] When the hydrogen bond donor is lactic acid and the hydrogen bond acceptor is one of L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 12:1;

[0019] When the hydrogen bond donor is one of ethanol and methanol, and the hydrogen bond acceptor is choline chloride, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 6:1.

[0020] Optimized, in the above method of recovering solid electrolyte in an all-solid-state lithium-ion battery using a low eutectic solvent, in step 2), the mass ratio of the all-solid-state lithium-ion battery electrolyte to the low eutectic solvent is 1:200-1:150.

[0021] In the technical solution of the present application, the method is simple to operate, low in cost, low in energy consumption, and green and pollution-free; the green solvent used - the low eutectic solvent is green, mild and environmentally friendly, easy to synthesize and operate, and has good biocompatibility. It has important research significance for the effective absorption of solid electrolytes of all-solid-state lithium-ion batteries and is in line with the concept of "sustainable development". DETAILED DESCRIPTION

[0022] The technical features of the present invention are further described below in conjunction with specific embodiments.

[0023] In the present application, a method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent is disclosed, and its main steps include:

[0024] 1) The hydrogen bond donor and the hydrogen bond acceptor are stirred and mixed to obtain a low eutectic solvent.

[0025] 2) Weighing an all-solid-state lithium-ion battery electrolyte, the mass ratio of the all-solid-state lithium-ion battery electrolyte to the low eutectic solvent is 1:200-1:150. Dissolving the weighed all-solid-state lithium-ion battery electrolyte into the low eutectic solvent for leaching, the leaching temperature is 25 degrees Celsius to 120 degrees Celsius, and the leaching time is 0.17 hours to 48 hours.

[0026] 3) After the reaction in step 2) is completed, a mixture is obtained, and the mixture is centrifuged to obtain an upper clear liquid and a lower mixture II.

[0027] 4) After step 3), equal volumes of the supernatant and antisolvent were mixed and ultrasonically treated for 20 minutes, and then allowed to stand for 24 hours to recover metals from the supernatant.

[0028] In this application, the types of hydrogen bond donors and hydrogen bond acceptors of the low eutectic solvent are optimized. After research and experiments, the hydrogen bond donors can be selected from acids, phenols, alcohols, salts or ketones, and the hydrogen bond acceptors can be selected from polyethylene glycol 200, choline chloride or amino acids. Specifically,

[0029] The hydrogen bond acceptor is one of polyethylene glycol 200, choline chloride, L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine. The hydrogen bond donor is one of benzoic acid, oxalic acid, phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, lactic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzenediol, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, ethanol, methanol, zinc chloride, ferric chloride, and acetylacetone.

[0030] The technical solution of the present application is applicable to electrolytes in all-solid-state lithium-ion batteries such as lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide and aluminum-doped lithium lanthanum zirconium oxide.

[0031] In the present application, the molar ratio of hydrogen bond donor to hydrogen bond acceptor may be 1:14, 1:10, 1:6, 6:1, 12:1, etc.

[0032] Specifically, when the hydrogen bond acceptor is polyethylene glycol 200 and the hydrogen bond donor is one of phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzene, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, zinc chloride, ferric chloride, and acetylacetone, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6.

[0033] When the hydrogen bond acceptor is polyethylene glycol 200 and the hydrogen bond donor is one of benzoic acid and oxalic acid, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6-1:14.

[0034] When the hydrogen bond donor is lactic acid and the hydrogen bond acceptor is one of L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 12:1.

[0035] When the hydrogen bond donor is one of ethanol and methanol, and the hydrogen bond acceptor is choline chloride, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 6:1.

[0036] The technical solution of the present application is further described in detail below in conjunction with specific embodiments.

[0037] Example 1

[0038] L-cysteine ​​and lactic acid in a molar ratio of 1:12 were added to a reagent bottle and heated and stirred at 80 degrees Celsius for 24 hours to generate an L-cysteine:lactic acid (1:12) type low eutectic solvent.

[0039] Weigh 5 g of L-cysteine:lactic acid (1:12) type low eutectic solvent and 0.1 g of lithium aluminum titanium phosphate into a reaction bottle and put in a magnetic bar. Put the reaction bottle into an oil bath pot, dissolve and recover at 80 degrees Celsius for 24 hours, and then stop heating and stirring.

[0040] The reaction bottle was taken out and the magnetic particles were sucked out with a magnet. The solid-liquid mixture after the reaction was transferred to a 15 ml centrifuge tube and centrifuged at 12,000 rpm for 20 minutes.

[0041] The upper layer of the solution in the centrifuge tube was aspirated and transferred to a 50 ml volumetric flask with a dropper, and the supernatant was diluted with 0.25 mol nitric acid to obtain the sample to be tested. The concentration of metal ions in the sample to be tested was then determined using an inductively coupled plasma emission spectrometer and the leaching efficiency was calculated.

[0042] The results show that under the conditions of 80 degrees Celsius and 24 hours, the leaching efficiency of lithium ions in lithium aluminum titanium phosphate by L-cysteine: lactic acid (1:12) is 58.80%, the leaching efficiency of aluminum ions is 52.80%, and the leaching efficiency of titanium ions is 18.80%.

[0043] Example 2

[0044] The difference between this embodiment and embodiment 1 is that the temperature is changed to 25 degrees Celsius, and other conditions remain unchanged. The leaching efficiency of lithium ions in lithium aluminum titanium phosphate by the L-cysteine:lactic acid (1:12) type low eutectic solvent is 36.82%, the leaching efficiency of aluminum ions is 27.36%, and the leaching efficiency of titanium ions is 8.58%.

[0045] Example 3

[0046] The difference between this embodiment and embodiment 1 is that the reaction temperature is continued to be changed to 40, 60, 100, and 120 degrees Celsius, and other conditions are not changed. Under different temperature conditions, the leaching efficiency of lithium, aluminum, and titanium ions in lithium aluminum titanium phosphate by L-cysteine: lactic acid (1:12) type low eutectic solvent is shown in Table 1.

[0047] Example 4

[0048] The difference between this embodiment and embodiment 1 is that the dissolution time of the low eutectic solvent and lithium aluminum titanium phosphate is changed to 0.17 hours, and other conditions remain unchanged. The leaching efficiency of lithium ions in lithium aluminum titanium phosphate by the L-cysteine:lactic acid (1:12) type low eutectic solvent is 37.70%, the leaching efficiency of aluminum ions is 20.82%, and the leaching efficiency of titanium ions is 7.19%.

[0049] Example 5

[0050] The difference between this embodiment and embodiment 1 is that the reaction time is changed to 1, 6, 12, 24, and 48 hours, and other conditions are not changed. The leaching efficiency of lithium, aluminum, and titanium ions in lithium aluminum titanium phosphate by L-cysteine: lactic acid (1:12) type low eutectic solvent at different dissolution times is shown in Table 1.

[0051] Example 6

[0052] The difference between this embodiment and embodiment 1 is that the mass of the low eutectic solvent is changed to 10 grams, and other conditions remain unchanged. The leaching efficiency of lithium ions in lithium aluminum titanium phosphate by the L-cysteine:lactic acid (1:12) type low eutectic solvent is 57.75%, the leaching efficiency of aluminum ions is 57.11%, and the leaching efficiency of titanium ions is 30.24%.

[0053] Example 7

[0054] The difference between this embodiment and embodiment 1 is that the mass of the low eutectic solvent is continued to be changed to 15 grams, and other conditions are not changed. Under different masses of low eutectic solvents, the leaching efficiency of lithium, aluminum and titanium ions in lithium aluminum titanium phosphate by L-cysteine: lactic acid (1:12) type low eutectic solvent is shown in Table 1.

[0055] Example 8

[0056] The difference between this embodiment and embodiment 1 is that the hydrogen bond donor in the L-cysteine: lactic acid (1:12) type low eutectic solvent is changed to a different type of amino acid, and other conditions remain unchanged. The leaching efficiency of lithium, aluminum, and titanium ions in lithium aluminum titanium phosphate by the green low eutectic solvent is shown in Table 1.

[0057] Example 9

[0058] The difference between this embodiment and embodiment 1 is that the amino acid type low eutectic solvent is changed to a polyethylene glycol type low eutectic solvent, that is, L-cysteine: lactic acid (1:12) is replaced by polyethylene glycol: zinc chloride (6:1), and other conditions are unchanged. The leaching efficiency of lithium ions in lithium aluminum titanium phosphate by the polyethylene glycol: zinc chloride (6:1) type low eutectic solvent is 66.50%, the leaching efficiency of aluminum ions is 52.76%, and the leaching efficiency of titanium ions is 5.25%.

[0059] Example 10

[0060] The difference between this embodiment and embodiment 9 is that the all-solid-state lithium-ion battery electrolyte is changed to lithium lanthanum zirconium tantalum oxide, and the leaching efficiency of lithium ions in lithium lanthanum zirconium tantalum oxide by the polyethylene glycol: zinc chloride (6:1) type low eutectic solvent is 82.20%, the leaching efficiency of lanthanum ions is 1.64%, the leaching efficiency of tantalum ions is 0.70%, and the leaching efficiency of zirconium ions is 0.70%.

[0061] Table 1. Recycling of lithium aluminum titanium phosphate electrolyte for all-solid-state lithium-ion battery by deep eutectic solvents

[0062] Solid electrolyte Solid electrolyte mass / g Deep eutectic solvents Mass of deep eutectic solvent / g Time / Hour Temperature / Celsius ηLi / % ηA1 / % ηTi / % Lithium Aluminum Titanium Phosphate 0.1 PEG200: zinc chloride = 6:1 5 24 80 66.50 52.76 5.25 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 80 58.80 52.80 18.80 Lithium Aluminum Titanium Phosphate 0.1 L-arginine: lactic acid = 1:12 5 24 80 52.30 51.80 23.30 Lithium Aluminum Titanium Phosphate 0.1 L-histidine: lactic acid = 1:12 5 24 80 52.20 54.10 23.30 Lithium Aluminum Titanium Phosphate 0.1 L-lysine: lactic acid = 1:12 5 24 80 50.50 53.90 21.20 Lithium Aluminum Titanium Phosphate 0.1 D-methionine: lactic acid = 1:12 5 24 80 50.30 94.00 20.10 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 25 36.82 27.36 8.58 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 40 39.97 36.19 12.49 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 60 39.91 38.37 16.27 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 80 58.8 52.8 18.8 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 100 53.33 43.85 19.63 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 24 120 56.32 48.11 14.91 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 0.17 80 37.7 20.82 7.19 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 1 80 39.88 35.76 11.97 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 6 80 43.32 40.86 17.49 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 12 80 46.04 42.95 19.04 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 36 80 48.4 44.49 21.45 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 5 48 80 51 48.23 23.27 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 10 24 80 57.75 57.11 30.24 Lithium Aluminum Titanium Phosphate 0.1 L-cysteine: lactic acid = 1:12 15 24 80 68.68 73.43 40.36

[0063] Embodiment 11

[0064] The difference between this embodiment and embodiment 9 is that the all-solid-state lithium-ion battery electrolyte is changed to aluminum-doped lithium lanthanum zirconium oxide, and the leaching efficiency of lithium ions in aluminum-doped lithium lanthanum zirconium oxide by the polyethylene glycol: zinc chloride (6:1) type low eutectic solvent is 64.00%, the leaching efficiency of lanthanum ions is 1.95%, the leaching efficiency of aluminum ions is 20.98%, and the leaching efficiency of zirconium ions is 1.92%.

[0065] Example 12

[0066] The difference between this embodiment and embodiment 11 is that the type of hydrogen bond donor of the low eutectic solvent is changed to alcohols, phenols, ketones, etc., and other conditions remain unchanged. The leaching efficiency of lithium ions from aluminum-doped lithium lanthanum zirconium oxide by the low eutectic solvent is shown in Table 2.

[0067] Embodiment 13

[0068] The difference between this embodiment and embodiment 10 is that the type of hydrogen bond donor of the low eutectic solvent is changed to alcohols, phenols, ketones, etc., and other conditions remain unchanged. The leaching efficiency of lithium ions in lithium aluminum titanium phosphate by the low eutectic solvent is shown in Table 3.

[0069] Embodiment 14

[0070] The difference between this embodiment and embodiment 11 is that the polyethylene glycol: zinc chloride (6:1) type low eutectic solvent is replaced by a polyethylene glycol: oxalic acid (6:1) type low eutectic solvent, and the polyethylene glycol: oxalic acid (6:1) type low eutectic solvent has a leaching efficiency of 31.70% for lithium ions in aluminum-doped lithium lanthanum zirconium oxygen of the all-solid-state lithium ion battery electrolyte, a leaching efficiency of 7.80% for aluminum ions, a leaching efficiency of 1.40% for zirconium ions, and a leaching efficiency of 0.019% for lanthanum ions.

[0071] The dissolution leaching experiment was carried out to optimize the experimental conditions of temperature, time, hydrogen bond donor-acceptor molar ratio, low eutectic solvent quality and all-solid-state lithium-ion battery electrolyte quality. The leaching efficiency of polyethylene glycol: oxalic acid (6:1) on the metal elements in the aluminum-doped lithium lanthanum zirconium oxygen of the all-solid-state lithium-ion battery electrolyte is shown in Table 2.

[0072] Embodiment 15

[0073] The difference between this embodiment and embodiment 14 is that the polyethylene glycol: oxalic acid (6:1) type low eutectic solvent is replaced with a polyethylene glycol: benzoic acid (6:1) type low eutectic solvent, and the temperature, time and quality of the low eutectic solvent are optimized by dissolution experiments.

[0074] The leaching efficiency of the polyethylene glycol:benzoic acid (6:1) type low eutectic solvent on the metal elements in the aluminum-doped lithium lanthanum zirconium oxide electrolyte of the all-solid-state lithium-ion battery is shown in Table 2.

[0075] Example 16

[0076] The difference between this embodiment and embodiment 15 is that the mass of 0.1 g of aluminum-doped lithium lanthanum zirconium oxide and 5 g of polyethylene glycol: oxalic acid (6:1) type low eutectic solvent is proportionally enlarged by 50 times, that is, 5 g of aluminum-doped lithium lanthanum zirconium oxide and 250 g of polyethylene glycol: oxalic acid (6:1) low eutectic solvent are weighed, and other conditions are unchanged. The leaching efficiency is measured as shown in Table 2.

[0077] Table 2. Recycling of aluminum-doped lithium lanthanum zirconium oxide electrolytes in all-solid-state lithium-ion batteries with deep eutectic solvents

[0078] Solid electrolyte Solid electrolyte mass / g Deep eutectic solvents Mass of deep eutectic solvent / g Time / Hour Temperature / Celsius ηLi / % ηLa / % ηA1 / % η Zr / % Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:resorcinol=6:1 5 24 80 85.00 1.00 16.30 1.10 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: phytic acid = 6: 1 5 24 80 85.50 41.10 224.20 36.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: acetylacetone = 6: 1 5 24 80 88.71 1.64 25.95 2.43 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:1, 2-benzenediol = 6:1 5 24 80 90.10 2.50 18.80 1.80 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:2-aminophenol=6:1 5 24 80 90.40 2.90 16.60 2.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: ascorbic acid = 6:1 5 24 80 93.40 4.40 8.10 2.60 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 Choline chloride: anhydrous ethanol = 1:6 5 24 80 94.50 0.25 24.20 0.80 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 Choline chloride: methanol = 1:6 5 24 80 97.60 0.03 22.60 0.90 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG200: p-toluic acid = 6:1 5 24 80 97.90 2.10 28.80 0.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 0.17 80 74.30 1.20 8.00 0.20 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 1 80 78.10 2.80 25.20 0.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 6 80 84.00 4.70 22.60 0.70 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 12 80 90.20 2.60 8.80 0.40 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 36 80 81.20 3.80 10.90 0.60 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 48 80 80.20 4.50 9.50 0.70 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 24 25 80.60 1.50 5.50 0.20 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 24 40 84.60 2.00 6.40 0.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 24 60 86.00 2.40 6.60 0.40 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 24 100 56.50 5.20 4.60 1.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 5 24 120 52.80 2.00 2.80 0.40 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 10 24 80 67.60 3.50 6.30 0.80 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200:benzoic acid=6:1 15 24 80 66.30 3.10 5.10 0.90 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 1 80 33.70 0.03 6.90 0.40 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 6 80 32.00 0.02 7.00 1.00 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 12 80 32.70 0.01 8.30 1.30 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 36 80 39.10 0.02 12.00 2.10 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 48 80 44.10 0.01 9.80 1.80 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 24 25 33.70 0.03 4.00 0.50 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG200: oxalic acid = 6:1 5 24 40 34.40 0.05 4.80 0.50 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 24 60 32.50 0.14 6.50 1.20 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 24 100 36.60 0.05 11.00 2.60 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 5 24 120 39.10 0.07 52.30 0.70 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 10 24 80 63.20 0.05 14.80 1.70 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 6:1 15 24 80 74.40 0.05 17.70 1.50 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.05 PEG 200: oxalic acid = 6:1 5 24 80 62.50 0.03 12.50 1.60 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.025 PEG 200: oxalic acid = 6:1 5 24 80 87.50 0.05 21.80 1.20 Aluminum-doped Lithium Lanthanum Zirconium Oxide 5 PEG 200: oxalic acid = 6:1 250 24 80 46.20 0.03 77.30 2.50 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 10:1 5 24 80 12.50 0.00 10.50 0.70 Aluminum-doped Lithium Lanthanum Zirconium Oxide 0.1 PEG 200: oxalic acid = 14:1 5 24 80 8.40 0.01 10.00 0.60

[0079] 2 ml of the leaching solution and 2 ml of the 70 antisolvents to be selected were respectively subjected to ultrasonic treatment for 20 minutes and allowed to stand for 24 hours. The precipitation formation was observed as shown in Table 4. "√" in Table 4 indicates that precipitation was generated.

[0080] Table 3. Recycling of solid electrolytes of all-solid-state lithium-ion batteries with deep eutectic solvents: Lithium lanthanum zirconium tantalum oxide

[0081] Electrolytes Electrolyte mass / g Deep eutectic solvents Mass of deep eutectic solvent / g Time / Hour Temperature / Celsius ηLi / % ηLa / % ηTa / % ηZr / % Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: parahydroxybenzoic acid = 6:1 5 24 80 86.50 2.31 0.20 1.10 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: thymol = 6:1 5 24 80 86.50 0.40 0.20 0.50 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 Choline chloride: methanol = 1:6 5 24 80 87.20 0.00 0.40 0.30 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: citric acid = 6:1 5 24 80 87.40 0.22 0.30 0.70 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: 1-naphthol = 6:1 5 24 80 91.00 0.20 0.10 0.50 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: formic acid = 6: 1 5 24 80 91.40 0.12 0.10 0.10 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: glacial acetic acid = 6:1 5 24 80 93.60 1.49 0.30 0.90 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200: ferric chloride = 6:1 5 24 80 94.10 16.15 0.20 5.10 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 PEG 200:levulinic acid = 6:1 5 24 80 94.20 4.77 0.30 2.00 Lithium Lanthanum Zirconium Tantalum Oxide 0.1 Choline chloride: ethanol = 1:6 5 24 80 99.50 0.00 0.30 0.30

[0082] Embodiment 17

[0083] The difference between this embodiment and embodiment 16 is that the polyethylene glycol: oxalic acid (6:1) type low eutectic solvent is replaced by a polyethylene glycol: benzoic acid (6:1) type low eutectic solvent, and other conditions remain unchanged. The leaching efficiency is measured and the anti-solvent experiment is performed on the leaching solution to observe the precipitate formation, see Table 4.

[0084] Table 4 Precipitation effect of anti-solvent experiment

[0085]

[0086] Of course, the above description is not a limitation of the present invention, and the present invention is not limited to the above examples. Any changes, modifications, additions or substitutions made by ordinary technicians in this technical field within the essential scope of the present invention should fall within the protection scope of the present invention.

Claims

1. A method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent, characterized in that: The following steps are involved: 1) stirring and mixing a hydrogen bond donor and a hydrogen bond acceptor to obtain a deep eutectic solvent; 2) weighing an all-solid-state lithium-ion battery electrolyte, and dissolving the weighed all-solid-state lithium-ion battery electrolyte into a deep eutectic solvent for leaching; 3) After the reaction in step 2) is completed, a mixture is obtained, and the mixture is centrifuged to obtain an upper clear liquid and a lower mixture II; In step 1), the hydrogen bond donor is an acid, a phenol, an alcohol, a salt or a ketone, and the hydrogen bond acceptor is polyethylene glycol 200, choline chloride or an amino acid.

2. The method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 1, characterized in that: The hydrogen bond acceptor is one of polyethylene glycol 200, choline chloride, L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine; The hydrogen bond donor is one of benzoic acid, oxalic acid, phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, lactic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzenediol, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, ethanol, methanol, zinc chloride, ferric chloride, and acetylacetone.

3. The method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 1, characterized in that: All-solid-state lithium-ion battery electrolytes include lithium aluminum titanium phosphate, lithium lanthanum zirconium tantalum oxide, and aluminum-doped lithium lanthanum zirconium oxide.

4. The method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 1, characterized in that: When leaching is performed in step 2), the leaching temperature is 25 degrees Celsius to 120 degrees Celsius, and the leaching time is 0.17 hours to 48 hours.

5. The method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 1, characterized in that: After step 3), metal recovery is performed from the supernatant, and the specific process includes: Equal volumes of the supernatant and antisolvent were mixed and sonicated for 20 minutes, followed by standing for 24 hours.

6. The method for recovering solid electrolyte in all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 2, characterized in that: When the hydrogen bond acceptor is polyethylene glycol 200, and the hydrogen bond donor is one of phytic acid, ascorbic acid, p-toluic acid, p-hydroxybenzoic acid, formic acid, citric acid, glacial acetic acid, levulinic acid, resorcinol, 1,2-benzene, 2-aminophenol, 1-naphthol, 1-methylnaphthol, thymol, zinc chloride, ferric chloride, and acetylacetone, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6; When the hydrogen bond acceptor is polyethylene glycol 200 and the hydrogen bond donor is one of benzoic acid and oxalic acid, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 1:6-1:14; When the hydrogen bond donor is lactic acid and the hydrogen bond acceptor is one of L-lysine, L-arginine, L-histidine, L-cysteine, and D-methionine, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 12:1; When the hydrogen bond donor is one of ethanol and methanol, and the hydrogen bond acceptor is choline chloride, the molar ratio of the hydrogen bond donor to the hydrogen bond acceptor is 6:

1.

7. The method for recovering solid electrolyte in an all-solid-state lithium-ion battery using a deep eutectic solvent according to claim 2, characterized in that: In step 2), the mass ratio of the all-solid-state lithium-ion battery electrolyte to the low eutectic solvent is 1:200-1:150.

Citation Information

Cited By

  • Leaching method of retired ternary lithium battery positive electrode material based on choline chloride-levulinic acid eutectic solvent

    CN122279220A